Knowledge-attitude and practice of Anthrax and brucellosis: Implications for zoonotic disease surveillance and control in pastoral communities of Afar and Somali region, Ethiopia. - Rea Tschopp; Ashenafi GebreGiorgis Kidanu (Public Library of Science (PLoS), 2024)
Background Anthrax and brucellosis are endemic national priority zoonotic diseases in Ethiopia. This study assess the possible factors explaining the current limited information available on animal and human cases in pastoral communities. Methods Two questionnaire surveys gathered data from 509 pastoralists and 51 healthcare providers between February and April 2019 in five districts of Afar and the Somali region (SRS). Results Among the 51 healthcare providers, 25 (49%) and 38 (74.5%) had heard of brucellosis, and anthrax, respectively. Of those, only 3 (12%) and 14 (36.8%) knew the symptoms of brucellosis and Anthrax. None of the Health Extension Workers knew any disease symptoms. Healthcare providers recalled two human cases of brucellosis and 39 cases of Anthrax in the last 12 months, based on symptom-based diagnosis. Pastoralists had a moderate level of knowledge about diseases in their animals, with over half (52.4%; n = 267/509) understanding that animals can transmit diseases to people. Overall, 280 out of 508 (55.1%) and 333 out of 507 (65.7%) pastoralists had heard of brucellosis and Anthrax, respectively. Among the latter, 282 (51.3%) knew at least one preventive measure for Anthrax. However, disease knowledge among women was poor. Despite their knowledge, pastoralists engaged in risky unprotected animal handling, animal product consumption/usage as well as husbandry behaviors exposing them to pathogens and favoring the spread of diseases. They identified Anthrax as the most important zoonosis (47.6%) and as one of top three diseases suspected to cause mortality in their livestock. Pastoralists highlighted lack of vaccine coverage, availability and their timely administration. Both, pastoralists and healthcare providers stated the lack of disease awareness and the unavailability of drugs in the market as important challenges. Health facilities lacked protocols and standard operating procedures for managing zoonotic diseases, and did not have access to laboratory confirmation of pathogens. Conclusion Our study revealed significant under-reporting of Anthrax and brucellosis, and weak prevention and response in humans, mostly associated with poor disease knowledge of healthcare providers. Ability to respond to animal outbreaks was limited by vaccine and drugs availability, timely vaccine administration and the mobility of pastoralists.